2013
DOI: 10.1103/physrevlett.111.085004
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Hydrodynamic Mix in High-Velocity, Highly Compressed Inertial Confinement Fusion Implosions

Abstract: Deuterium-tritium inertial confinement fusion implosion experiments on the National Ignition Facility have demonstrated yields ranging from 0.8 to 7×10(14), and record fuel areal densities of 0.7 to 1.3 g/cm2. These implosions use hohlraums irradiated with shaped laser pulses of 1.5-1.9 MJ energy. The laser peak power and duration at peak power were varied, as were the capsule ablator dopant concentrations and shell thicknesses. We quantify the level of hydrodynamic instability mix of the ablator into the hot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 225 publications
(66 citation statements)
references
References 36 publications
(48 reference statements)
2
63
0
Order By: Relevance
“…The 3D flow approaches a value of = 0.85 for late time, while the 2D flow reaches a value of 0.7 at t = 0.006s. The temporal evolution of in two-and three-dimensions rapidly increases immediately after the reshock as can be seen in Figure 2 Recent ICF experiments 4,10 have demonstrated that as more ablator material atomically mixes with the D-T fuel the fusion yield will decrease. Indeed 1D and 2D calculations have been unable to match experiments where mixing is present.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The 3D flow approaches a value of = 0.85 for late time, while the 2D flow reaches a value of 0.7 at t = 0.006s. The temporal evolution of in two-and three-dimensions rapidly increases immediately after the reshock as can be seen in Figure 2 Recent ICF experiments 4,10 have demonstrated that as more ablator material atomically mixes with the D-T fuel the fusion yield will decrease. Indeed 1D and 2D calculations have been unable to match experiments where mixing is present.…”
mentioning
confidence: 92%
“…Of particular interest is the effect of dimensionality on the amount of mass which becomes atomically mixed due to the instability. The amount of mixed mass may directly impact the observed fusion yield 10 of Inertial Confinement Fusion (ICF) capsule implosions and speculation 4 still exists as to whether dimensional effects can account for discrepancies between experiment and simulation.…”
mentioning
confidence: 99%
“…N120205 and N120213 had the same laser pulse request at P laser ¼ 440 TW. While N120205 (Au) performed comparatively well achieving T ion of 3.4 keV, on N120213 (DU) T ion dropped to 1.9 keV and yield plummeted by a factor of 6× due to CH ablator material catastrophically mixing into the hot spot [8]. Conversely, the highest DSR and thus fuel ρR reported so far was achieved with a DU hohlraum on N120321 [6].…”
Section: Fig 4 (Color Online)mentioning
confidence: 92%
“…However, some of them showed evidence for significant amounts of CH ablator material mixing into the hot spot [8,9], degrading the implosion performance. To increase the resistance to hydrodynamic instabilities [10], the "high-foot" drive design was developed [11,12], which has demonstrated an order-of-magnitude improvement in neutron yields with first evidence for additional heating from alpha particle stopping [13].…”
mentioning
confidence: 99%
“…In order to increase the significance of the measurements from SPIDER, the absolute characterization of the spectral sensitivity was executed at the High Energy X-ray (HEX) lab [7] at the National Security and Technologies, LLC (NSTec) Livermore facility. A determination of the absolute x-ray yield would be useful in several ways: (1) To gauge the relative quality of implosions or back-lighter strength among NIF experiments; (2) as an input parameter into a model that estimates the amount of material mixing that occurs from the capsule outer shell into the fuel layers of the DT capsule [8]; (3) If the x-ray yield is predicted for a particular experiment, then appropriate filtering can be chosen for SPIDER to optimize the dynamic range of the recorded signal. In addition, characterization was performed utilizing three different photocathodes: CsI with a thickness of 0.2 µm, 1.0 µm and 10 µm in order to determine which one is more efficient in the typical implosion energy range.…”
Section: Introductionmentioning
confidence: 99%